Food appraisal: Explaining tourists’ willingness to pay more for organic food - Rodrigues, A.; Loureiro, S. M. C.; Nascimento, J. (Journal of Hospitality and Tourism Insights, 2026)
Purpose This study is grounded in appraisal theory to examine the factors influencing tourists’ attitudes toward organic food and their willingness to pay a premium in rural tourism destinations. Design/methodology/approach A mixed-method approach was adopted. A focus group with seven participants explored culinary preferences and ecological awareness. This was followed by an on-site survey of 396 tourists, which analyzed the relationships among food consumption tendencies, food ecological welfare and ecological self-identity using structural equation modeling. Findings Results revealed that tourists’ attitudes toward organic food are shaped by food consumption tendencies (modern, fusion or local cuisine) and ecological welfare considerations, mediated by ecological self-identity. Attitude was the central mediator, driving willingness to pay a premium for organic food experiences. Research limitations/implications Data were collected in a single rural location, which limits generalizability. Future research should extend the model to diverse contexts and populations to enhance its applicability. Practical implications Destination managers should emphasize the availability of organic food and its offerings’ ecological benefits. Effective communication strategies highlighting sustainability practices can boost consumer willingness to pay a premium. Social implications Promoting organic food consumption aligns with global sustainability goals, fostering ecological awareness and responsible tourist behaviors. Originality/value These studies uniquely integrate ecological self-identity and appraisal theory to explain tourists’ willingness to pay more for organic food. Thus, this research contributes to the literature by providing valuable insights about psychological and cognitive factors influencing consumers’ attitudes and behaviors toward organic food consumption.